Paraoxonasa 1 (PON1) y su relación con el perfil lipídico y la Lipoperoxidación en una población adulta de la ciudad de cerro de pasco, 4330 m. - Carranza A, Elizabeth (2012)
In order to analyze the activity of the serum enzyme paraoxonase, phenotype distribution and its relationship with lipid profile and oxidative stress, in an elderly population from Cerro de Pasco city(4330 m), were studied blood serum of 30 men aged 60 years and 40 postmenopausal women. Paraoxon were used as substrate for measuring the activity of paraoxonase basal and stimulated with NaCl 1 M and measuring phenylacetate arylesterase activity. The lipid profile was measured using commercial kits, apolipoproteins A-1 and B by turbidimetric methods and malondialdehyde with thiobarbituric acid. The mean values of lipid profile, APO B, and malondialdehyde (expressed as TBARS) between men and women do not differ significantly. APO A-1 is significantly higher in women than in men. The activities of the PON 1 basal and stimulated not differ significantly between the two groups. There was significant difference in arylesterase activity in women compared to men. No correlation was found between paraoxonase activity and other parameters studied. Arylesterase activity correlates positively with APO A-1 (p<0,05), but not with HDL-cholesterol, APO B and TBARS. In conclusion, the lipid profile, APO A-1, APOB and TBARS demonstrate that elderly people living at high altitudes could be better protected against cardiovascular disease.